2022
DOI: 10.47307/gmc.2022.130.s1.35
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Adolescents’ Religiosity and Resilience through Islamic Spiritual Mindfulness

Abstract: Adolescence is a transitional period between childhood and adulthood, making it prone to various deviant behaviors due to dramatic bio-psycho-social and spiritual maturity changes. Islamic spiritual mindfulness is an effort to build self-awareness that drives an individual to do good deeds. This study aimed to determine the effects of Islamic spiritual mindfulness on increasing religiosity and resilience among Indonesian adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…39 Resilience enables adolescents to persevere, adapt, and rise to the occasion when faced with difficult circumstances. 40 Our study revealed substantial and lasting improvements in mindfulness and resilience, with medium to high effect sizes immediately post-intervention and persisting at the 3-month follow-up. These findings underscore the efficacy of the MBSI online program in fostering enduring and positive impacts in these vital domains.…”
Section: Discussionsupporting
confidence: 47%
“…39 Resilience enables adolescents to persevere, adapt, and rise to the occasion when faced with difficult circumstances. 40 Our study revealed substantial and lasting improvements in mindfulness and resilience, with medium to high effect sizes immediately post-intervention and persisting at the 3-month follow-up. These findings underscore the efficacy of the MBSI online program in fostering enduring and positive impacts in these vital domains.…”
Section: Discussionsupporting
confidence: 47%